The Importance of Indonesian Language Education Among Teenagers (International Journal of Economics Management and Social Science, 2023)
This study investigates challenges confronting the Indonesian language among teenagers, focusing on declining formal linguistic competence caused by slang dominance, excessive code-mixing, and historical disconnect from its philosophical foundation as a unifying national identity. Using qualitative library research, the analysis of scholarly sources reveals four critical impacts: (1) disrupted learning processes as linguistic errors become normalized; (2) marginalization of Indonesian amid preference for exclusive slang; (3) communication barriers in formal contexts due to register confusion; and (4) diminished dignity as the language is perceived as outdated. Revitalization requires a holistic strategy: contextual education fostering critical awareness of language appropriateness, strengthening digital ecosystems with quality Indonesian content, reconnecting youth with the 1928 Youth Pledge's inclusive philosophy through relevant narratives, and multisectoral synergy among families, schools, and government under the principle "Prioritize Indonesian, Preserve Regional Languages, Master Foreign Languages." While linguistic evolution is natural, mastering standard Indonesian remains essential for effective cross-context communication and sustaining national identity in the digital era.